The Influence of Ownership Structure, Current Tax Expense, Deferred Tax Expense and Tax Planning on Profit Management - Christy Theodora*; Wahyu Prasetyo (Universitas Syiah Kuala, 2023)
The purpose of this study was to examine the effect of the ownership structure, deferred tax expense, current tax expense and tax planning on earnings management. This study used 112 manufacturing companies which were used as research samples which were analyzed using quantitative methods. The sample in this study was tested using multiple linear regression analysis using SPSS version 24. Through the research that has been tested, the researchers obtained the results that: institutional ownership has a significant negative effect on earnings management, managerial ownership has a significant negative effect on earnings management, current tax expense has a significant positive effect on earnings management, deferred tax expense has a negative effect on earnings management, and tax planning has no effect on earnings management.